Respon Pemupukan Terhadap Hasil dan Kualitas Hasil Salak Gula Pasir (Salacca zalacca cv. Gula Pasir) di Luar Musim Serta Kandungan Air Dan Klorofil Daun - DEWI, NI MADE KESUMA; RAI, I NYOMAN; WIRAATMAJA, I WAYAN (Agrotrop : Journal on Agriculture Science; Vol 10 No 1 (2020)DO - 10.24843/AJoAS.2020.v10.i01.p10, 2020)
Fertilization Response to Off-Season Production and Fruit Quality of Salak Gula Pasir ( Salacca Zalacca cv. Gula Pasir) and water and Chlorophyll Content of Leaves. Naturally salak Gula Pasir ( Salacca zalacca cv. Gula Pasir) flowers every three months a year, but only one to two seasons of the flowers can develop into fruit. Failure of flowers develop into fruit, usually call fruit-set failure, causes the fruits be available seasonally in a short time period, only 2-3 months a year, i.e. during the harvest time (on-season period) from December to February. This research aimed to know response of fertilization to off-season production and fruits quality of salak Gula Pasir and its ralatinship to water and chlorophyll content of leaves. The study used a randomized block design with the treatment was fertilization, consists of 14 levels (fertilized according farmers’ way with leaf midrib only/control, fertilized with compost, mycorrhizal biofertilizer, inorganic NPK, combination of farmers' way and compost, combination of farmers’ way and mycorrhizal biofertilizer,  combination of farmers' way and inorganic NPK, combination of compost and mycorrhizal biofertilizer,  combination of compost and inorganic NPK,  combination of mycorrhizal and inorganic NPK,  combination of farmers’ way, compost, and mycorrhizal biofertilizer,  combination of farmers’ way, compost, inorganic NPK,  combination of farmers’ way, mycorrhizal biofertilizer and inorganic NPK, and  combination of farmers’ way, compost, mycorrhizal biofertilizer, and inorganic NPK). Each treatment was repeated 3 times. The study was carried out in the off season period from April to Nopember 2018 at the production center of salak Gula Pasir plantation i.e. at Sibetan Village, Bebandem District, Karangasem Regency. The results showed that the highest fruit weight per tree at the off-season was obtained on combination of fertilization of farmers' way and mycorrhizal biofertilizer  (of 2536.67 g) and the lowest was on  control/fertilized according farmers’ way  (1,220.00 g). Fertilization with compost, mycorrhizal biofertilizer, and inorganic NPK singly, or by combining it, increases the quality of off-season fruit of salak Gula Pasir, reflected by the increase of weight per fruit, fruit diameter and fruit sweetness compared to control. The lower of yield per tree and quality of fruit on control compared to other fertilization treatments was relate to low relative water content and chlorophyll content of leaves.